Effects of Different Tissue Flossing Applications on Range of Motion, Maximum Voluntary Contraction, and H-Reflex in Young Martial Arts Fighters - Kalc, Miloš; Mikl, Samo; Žökš, Franci; Vogrin, Matjaž; Stöggl, Thomas (Frontiers in Physiology, 2021)
The purpose of this study was to investigate the effects of tissue flossing applied to the ankle joint or to the calf muscles, on ankle joint flexibility, plantarflexor strength and soleus H reflex. Eleven young (16.6 ± 1.2 years) martial arts fighters were exposed to three different intervention protocols in distinct sessions. The interventions consisted of wrapping the ankle (ANKLE) or calf (CALF) with an elastic band for 3 sets of 2 minutes (2 minutes rest) to create vascular occlusion. A third intervention without wrapping the elastic band served as a control condition (CON). Active range of motion for ankle (AROM), plantarflexor maximum voluntary contraction (MVC) and soleus H reflex were assessed before (PRE), after (POST) and 10 minutes after (POST10) the intervention. The H reflex, level of pain (NRS) and wrapping pressure were also assessed during the intervention. Both CALF and ANKLE protocols induced a significant drop in H reflex during the intervention. However, the CALF protocol resulted in a significantly larger H reflex inhibition during and after the flossing intervention (medium to large effect size). H reflexes returned to baseline levels 10 minutes after the intervention in all conditions. AROM and MVC were unaffected by any intervention. The results of this study suggest that tissue flossing can inhibit the muscle soleus H reflex particularly when elastic band is wrapped around the calf muscles. However, the observed changes at the spinal level did not translate into higher ankle joint flexibility or plantarflexor strength.